Measuring economic ill-being using objective and subjective indicators: evidence for the Philippines - Beja, Edsel L, Jr (Archīum Ateneo, 2015)
The mismatch between a country’s macroeconomic performance and the people’s economic well-being represents the overall economic ill-being in a society. This mismatch is measurable using objective indicators such as the inflation rate and the joblessness rate as well as subjective indicators such as personal evaluations on the inflation and joblessness rates. That is, the inflation rate shows the affordability of goods and services; and the subjective evaluation indicates whether people see the goods and services as affordable or not. In addition, the joblessness rate indicates the portion of the labor force that does not enjoy gainful employment; and the subjective evaluation indicates whether people see themselves as jobless or not. The results for the Philippines show a high-level of overall economic ill-being especially in the decade covering 2005 to 2014. This finding unveils a different scene from what the mainstream discourses are portraying as the current state of the Philippine society.